Metal organic framework membranes for separation applications. (May 2015) - Lin, YS
Graphical abstract: Highlights: Thin MOF membranes can be synthesized by secondary and in situ growth methods. MOF membranes offer exceptional gas separation characteristics. Thermal and chemical stability of MOF membranes in gas and liquid remains unclear. MOF membranes need improved permeance on support of large surface area. Abstract : Microprous metal organic framework materials possess unique properties as membrane materials for gas and liquid separation. An increasing number of metal organic framework membranes have been synthesized. Most studies were focused on more stable zeolitic imidazolate framework membranes for gas separation. Thin metal organic framework membranes are synthesized on porous inorganic or polymer supports by seeded secondary growth or in situ (counter-diffusion) synthesis methods. These membranes exhibit unique gas separation properties, such as high H2 /CO2 selectivity, unattainable to other microporous inorganic or polymer membranes. However, much less studies have been reported on the liquid separation properties and stability of metal organic framework membranes. To make metal organic framework membranes a viable separation technology requires understanding of the thermal and chemical stability of metal organic framework materials and membranes, and development of cost-effective synthesis of metal organic membranes with high permeance or on more easily scalable supports.